The role of arginase estimation to predict hypertensive disorder of pregnancy at an earlier stage - Saba Shafiq; Khan, Muhammad Nadim Akbar; Qayyum, Shazia; Sultana, Saadia (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the significance of serum arginase estimation as a predictor of pregnancy-induced hypertension and preeclampsia at an early stage. Method: The observational, cross-sectional study was conducted from October 15, 2021, to October 15, 2022, at the Department of Chemical Pathology, in collaboration with the Department of Obstetrics and Gynaecology, Pakistan Railway Hospital, Islamic International Medical College Trust, Rawalpindi, Pakistan, and comprised pregnant women with 20-25 weeks of gestation who were divided into three groups. Those having no complications were placed in control group A, those with pregnancy-induced hypertension in group B, and those with preeclampsia in group C. Serum arginase, uric acid, alanine transaminase, platelet count and spot urinary protein levels were measured for each subject. Data was analysed using SPSS 26. Results: Of the 90 women, 30(33.3%) were in group A with mean age 27.27±2.90 years, 30(33.3%) were in group B with mean age 30.17±2.48 years, and 30(33.3%) were in group C with mean age 29.33±3.11 years. There were significant intergroup differences in the mean levels of serum arginase, serum uric acid, alanine transaminase, platelet count and spot urinary protein (p<0.05). Conclusion: A moderate to marked increase in serum arginase levels in pregnancy-induced hypertension and preeclampsia cases, combined with abnormal serum uric acid and alanine transaminase levels along with low platelet count suggested that serum arginase estimation could be used to predict hypertensive disorders of pregnancy at an early stage. Key Words: Arginase, Preeclampsia, Pregnancy-induced hypertension.